1996
DOI: 10.1080/009841096161663
|View full text |Cite
|
Sign up to set email alerts
|

Lead in Human Blood From Children Living in Campania, Italy

Abstract: Blood lead (PbB) levels were determined in children living in Campania (in Naples and in a rural zone in the district of Caserta). Atmospheric lead (PbA) concentration in these considered areas was monitored for 1 yr (1993-1994). The children tested were questioned about common sources of lead, other than atmospheric, relating to their living and dietary habits. The PbB levels in children living in Naples were, at the 50th percentile, 13.8 micrograms/dl in males and 13.7 micrograms/dl in females; in children l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Blood concentrations are also comparable to those observed in children and adolescents from urban and rural areas of Campania region (Perrone et al, 1999), indicating safe, decreasing hematic lead concentrations in the area with respect to a previous, similar work by Amodio-Cocchieri et al (1996).…”
Section: Resultssupporting
confidence: 77%
“…Blood concentrations are also comparable to those observed in children and adolescents from urban and rural areas of Campania region (Perrone et al, 1999), indicating safe, decreasing hematic lead concentrations in the area with respect to a previous, similar work by Amodio-Cocchieri et al (1996).…”
Section: Resultssupporting
confidence: 77%
“…In children, these studies have shown an association between blood level poisoning and diminished intelligence, lower intelligence quotient-IQ, delayed or impaired neurobehavioral development, decreased hearing acuity, speech and language handicaps, growth retardation, poor attention span, and anti social and diligent behaviors [178, 179, 184, 185]. In the adult population, reproductive effects, such as decreased sperm count in men and spontaneous abortions in women have been associated with high lead exposure [186, 187].…”
Section: Leadmentioning
confidence: 99%
“…[14,33,60] It is well known that the hematopoietic system is one of the most important target organs of Pb toxicity. [61,62] Literature studies have shown that erythrocytes have a high Pb affinity and subjects exposed to air Pb who had anemia, also had plasma Pb levels significantly higher compared with a non-exposed control group.…”
Section: Discussionmentioning
confidence: 99%